Effects of microvascular invasion on clinical outcomes after resection with curative intent for cholangiocarcinoma. Issue 52 (24th December 2020) - Song, Bo-Hye; Cha, Boram; Park, Jin-Seok; Jeong, Seok; Lee, Don Haeng
Abstract : Abstract: Surgery is the only curative treatment for cholangiocarcinoma, but even after surgery, survival rates are unsatisfactory. Recently, several reports have suggested microvascular invasion (MiVi) is associated with poor postoperative prognosis in hepatocellular carcinoma (HCC). We considered that MiVi might be associated with poor clinical outcomes in patients with surgically resectable cholangiocarcinoma. The records of 91 patients who underwent resection with curative intent for cholangiocarcinoma at Inha University Hospital from 2007 to 2017 were comprehensively reviewed for clinicopathological characteristics, DFS, and overall survival (OS) relations between these factors and the presence of MiVi. Forty-nine of the 91 study subjects had MiVi and 42 did not. Median overall survivals were 492 days in the MiVi group and 1008 days in the noMiVi group and median DFSs were 367 days and 760 days, respectively. Cumulative survival ratio and recurrence incidence rates were significantly different in the 2 groups ( P = .012). Multivariable analysis showed the presence of MiVi was an independent risk factor of OS (hazard ratio [HR] 3.34; 95% confidence interval [CI], 1.40–7.97; P = .007). Cholangiocarcinoma is known to have a poor prognosis. When microvascular invasion remains after surgery it is associated with poor clinical outcomes.